Glutamate-mediated inhibition of oxidative phosphorylation in cultured retinal cells - Rego, Ana Cristina (1999)
Glutamate is an excitotoxin responsible for causing neuronal damage associated with mitochondria dysfunction. We have analyzed the relationship between the mitochondrial respiratory rate, the membrane potential ([Delta][Psi]) and the activity of mitochondrial complexes in retinal cells in culture, used as neuronal models. Glutamate (10 [mu]M-10 mM) dose-dependently decreased the O2 consumption and the membrane potential. A linear correlation was found between these parameters, suggesting that the mitochondrial respiratory function was affected. Exposure to glutamate (100 [mu]M) for 10 min, in the absence of Mg2+, inhibited the activity of complex I (26.3%), complexes II/III (22.2%) and complex IV (26.7%). MK-801 ((+)-5-methyl-10,11-dihydro-5H-dibenzo[a,d]-cyclohepten-5,10-imine hydrogen maleate), a non-competitive antagonist of the NMDA (N-methyl--aspartate) receptors, completely reversed the effect exerted by 100 [mu]M glutamate at the level of complexes I, II/III and IV. These results suggest that NMDA receptor-mediated inhibition of mitochondrial respiratory chain complexes may be responsible for the alteration in the respiratory rate of chick retinal cells submitted to glutamate.